Human Resource Management in Developing Teacher Professionalism Through Teacher Professional Education in Madrasah - Ulya, Kiswatuna; Hamid, Abdul; Hayati, Nur (Al-Qalam Institue, 2025)
This study aims to analyze human resource management in developing teacher professionalism through Teacher Professional Education (PPG) in madrasahs. The method used is a qualitative approach of case study type, with data collection techniques through in-depth interviews and observations. The data analysis technique used is thematic analysis, which helps in identifying important patterns related to human resource management in madrasahs. The results of the study indicate that human resource planning in this madrasah is carried out comprehensively, with teacher selection prioritizing academic qualifications and practical skills. The training provided combines theory and practice, and provides teachers with flexibility to choose training according to their needs. The implication of this study is that good human resource management, by paying attention to appropriate selection and relevant training, can improve the quality of teaching and teacher professionalism in madrasahs. This study also contributes to enriching the literature on human resource management in the madrasah education sector.